New horizons of vehicle aerodynamics. (August 2017) - Jessing, Christoph; Stoll, Daniel; Kuthada, Timo; Wiedemann, Jochen
Vehicle aerodynamics and wind tunnel technology are progressing towards more realistic simulations of the real-world on-road environment. This paper presents an overview of the new systems which were implemented during the recent wind tunnel upgrade at Forschungsinstitut für Kraftfahrwesenund Fahrzeugmotoren Stuttgart as well as comparable computational fluid dynamics simulations. The fully interchangeable road simulation system features an interchangeable five-belt system and three-belt system in the same full-scale automotive wind tunnel. This system offers the efficiency of a five-belt system combined with the more sophisticated ground simulation technique of a wide belt system, which is necessary to assess the aerodynamic properties of sports cars and racing cars. In order to simulate on-road wind conditions, a side-wind generator can be installed to generate a turbulent flow field in the wind tunnel test section. It could be shown that the commonly determined drag coefficient at 0° yaw angle in the smooth flow environment of today's wind tunnels is not representative of the drag found in real on-road wind conditions. Additionally, the investigations in unsteady side-wind conditions indicate that the commonly used approach to determine the side-wind sensitivity of a vehicle underestimates the forces occurring in turbulent flow conditions. A validated simulation model is presented. The simulation results are in good agreement with the experimental results and can be used as a complementary tool when assessing the unsteady aerodynamic behaviour of a vehicle; this behaviour can be coupled to a vehicle dynamics model for virtual road testing in the Stuttgart full-motion driving simulator. The unsteady-behaviour effects can be evaluated comprehensively, and the results allow a subjective assessment of the unsteady response of the vehicle. Furthermore, the aeroacoustic wind noise in on-road wind conditions is investigated during the development of the vehicle. The side-wind generator reproduces the natural stochastic cross-wind and allows the effect of these wind conditions to be investigated in the aeroacoustic wind tunnel. The results show similar ratings to those in on-road tests when compared with subjective listening tests. In summary, the techniques introduced open up new horizons in the field of vehicle aerodynamics and aeroacoustics, which are a step closer towards real-world conditions in automotive engineering.